Isbat Nikah dan Problematika Hukumnya: Tinjauan Yuridis, Sosiologis, dan Filosofis dalam Perspektif Maqashid Syariah - Mulyadi, Mulyadi (Sharia Journal and Education Center Publishing, 2025)
Unregistered marriages remain a significant issue in the Islamic family law system in Indonesia. The absence of official marriage registration leads to numerous legal and social consequences, particularly affecting women and children. Although isbat nikah (marriage validation through the religious court) is intended as a legal remedy, its implementation faces several challenges, ranging from bureaucratic complexity to court decisions that do not always uphold substantive justice. This study analyzes the problems surrounding isbat nikah from juridical, sociological, and philosophical perspectives using the framework of maqasid al-shariah. Employing a normative-sociological qualitative approach, the study examines legal statutes, judicial decisions, and Islamic jurisprudence to explore the extent to which maqasid al-shariah is realized in legal practice. The findings reveal that the prevailing legal approach remains formalistic, often neglecting the protection of women's and children's rights. When applied contextually and progressively, maqasid al-shariah can serve as a new paradigm for reforming Islamic family law toward a more just and welfare-oriented system.